Penegakan Hukum Terhadap Pelaku Kejahatan Pedofilia (Kelainan Seksual) - Maria Ana Liwa; Aji Titin Roswitha Nursanthy; Emilia Bernadetha Astuty (LPPM STIH Awang Long, 2020)
Pedophilia is a sexual disorder in the form of sexual desire for adolescents or children under the age of 14 years. People who suffer from pedophilia are called pedophiles. A person can be considered a pedophile if he is at least 16 years old. Pedophilia is known as child abuse, and it is important to know that pedophilia is a disease. Not all pedophiles abuse children, and not all people who abuse children are pedophiles. Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection in Article 290 regulates these criminal acts. But these sanctions do not cause a deterrent effect for perpetrators. This research is a library research that aims to analyze positively the criminal act of pedophilia so that this research is descriptive analytic. In this study, the author uses a juridical-normative and sociological approach, namely research with the aim of finding legal doctrines or principles related to pedophilia crimes, so that it is expected to be able to analyze clearly the Indonesian positive legal views on pedophilia crimes with data collection techniques. through a review of library materials related to these problems.